2021
DOI: 10.1039/d1sm00843a
|View full text |Cite
|
Sign up to set email alerts
|

A simulation study on the effect of nanoparticle size on the glass transition temperature of polymer nanocomposites

Abstract: The effect of the size of nanoparticles, σNP, on the glass transition temperature, Tg, of polymer nanocomposites is studied by using molecular dynamics simulations. The variation of Tg with σNP...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In particular, Khan et al reported that at a high volume fraction of NPs, the T g shows an increasing trend, with an increase in the amount of NPs due to the higher number of contacted polymer chains with NPs and the diffusion of NPs. They concluded that the T g can be controlled by the agglomeration of NPs and the interaction strength between the NPs and polymer chains [ 51 , 52 ]. In our case, this concentration is not reached in the experimental space scanned and the T g is only affected by the addition of OLA.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, Khan et al reported that at a high volume fraction of NPs, the T g shows an increasing trend, with an increase in the amount of NPs due to the higher number of contacted polymer chains with NPs and the diffusion of NPs. They concluded that the T g can be controlled by the agglomeration of NPs and the interaction strength between the NPs and polymer chains [ 51 , 52 ]. In our case, this concentration is not reached in the experimental space scanned and the T g is only affected by the addition of OLA.…”
Section: Resultsmentioning
confidence: 99%
“…Polymer nanocomposites possess attractive material properties that are unattainable with either base component. However, a complete description of these material properties is challenging because they depend on myriad parameters, including interaction strength, processing conditions, , nanofiller size and shape, and many others. In particular, the physical origin of exceptional performance enhancement offered by ultrasmall (∼1–2 nm diameter) polyhedral silsesquioxane (POSS) nanofillers remains relatively unexplored compared to larger (∼10 nm) fillers.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] The properties of polymers can be tuned by changing the size and volume fraction of NPs as well as the interaction between NPs and polymers. [11][12][13][14][15] It was pointed out that the attractive interactions between NPs and polymers have significant effects on the conformational and dynamical properties of polymer chains. 11,[13][14][15][16] For example, the diffusion coefficient (D) of poly(methyl methacrylate) (PMMA) decreased upon increasing the load of clay, while it roughly remained the same in a non-attractive polystyrene (PS)/ clay composite.…”
Section: Introductionmentioning
confidence: 99%